A Comparative Observational Study of the Use of Saline Uterine Hydrosonography for the Diagnosis and Assessment of Uterine Cavity Lesions in Women. (11th August 2016) - Vathanan, Veluppillai; Armar, Nii Adjeidu
Abstract : Aim of this study was to evaluate the performance of saline hydrosonography (HSGM) (also known as saline infusion sonography (SIS)) against transvaginal ultrasound scan (TVS) and hysteroscopy in the diagnosis of uterine cavity lesions. Diagnostic hysteroscopy with biopsy is considered as the "gold standard" to diagnose intrauterine abnormalities. The introduction of HSGM has improved the diagnostic capability of ultrasound. It is important to establish the efficacy and safety of HSGM before it is widely recommended for use. This retrospective observational data was collected from all 223 patients who underwent TVS, HSGM, and hysteroscopy as part of their gynaecological investigations from 1 January 2008 to 31 December 2010 at Central Middlesex Hospital, London. Endometrial Polyps . TVS: sensitivity 60.53%, specificity 97.06%, positive predictive value (PPV) 95.83%, and negative predictive value (NPV) 68.75% and HSGM: sensitivity 95%, specificity 97.14%, PPV 97.44%, and NPV 94.44%. Submucous Leiomyoma . TVS: sensitivity 57.14%, specificity 93.48%, PPV 84.21%, and NPV 78.18% and HSGM: sensitivity 96.55%, specificity 100.00%, PPV 100.00%, and NPV 97.92%. Diagnostic efficacy of HSGM is superior to TVS for the diagnosis of endometrial polyps and submucous fibroids. HSGM should be considered as an intermediate investigation after TVS to assess intracavity pathology and to confirm the diagnosis; hysteroscopy should become a therapeutic intervention.